Influence of Glutamic Acid on the Endogenous Respiration of Bacillus subtilis - Clifton, C. E. (1966)
Clifton, C. E. (Stanford University, Stanford, Calif.), and John Cherry. Influence of glutamic acid on the endogenous respiration of Bacillus subtilis. J. Bacteriol. 91:546–550. 1966.—Amino acids serve as the major initial endogenous substrate for Bacillus subtilis. The endogenous activity of freshly harvested washed cells is high and falls off rapidly with time of shaking at 30 C to lower but still significant levels. The rate of O(2) consumption after the addition of glutamic acid also decreases as the cells age, but more slowly than noted for endogenous respiration. When cells were fed glutamate as soon as possible after harvesting, an apparent stimulation of endogenous respiration was noted. However, endogenous activity was inhibited if the cell suspensions were shaken for at least 1 hr before addition of the glutamate. Similar results were obtained with glycerol or glucose as exogenous substrates. Variation in rates of respiration with age of the cells, inherent instability of B. subtilis, and possible utilization of substances initially excreted by the cells appear to account for the variations noted regarding the influence of an exogenous substrate on endogenous respiration.